2019
DOI: 10.1002/hbm.24816
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear interrelations show fundamentally distinct network structure in preictal intracranial EEG of epilepsy patients

Abstract: Resection of the seizure generating tissue can be highly beneficial in patients with drug-resistant epilepsy. However, only about half of all patients undergoing surgery get permanently and completely seizure free. Investigating the dependences between intracranial EEG signals adds a multivariate perspective largely unavailable to visual EEG analysis, which is the current clinical practice. We examined linear and nonlinear interrelations between intracranial EEG signals regarding their spatial distribution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
(88 reference statements)
1
12
0
Order By: Relevance
“… Indicated are the post-surgical seizure control according to the Engel classification scheme, durations of the included epochs, the location of seizure onset, etiological factors, the type of resection, the total number of artifact free channels, and the number of channels recording from RBT. Nineteen of these patients were already included in our preceding study ( 32 ) and are indicated by an asterisk *. One patient (p5) had two implantation schemes before resection, one patient (p29) had two distinct implantation schemes both followed by resection, and one patient (p28) had a second implantation after the surgical removal of brain tissue but no second resection .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“… Indicated are the post-surgical seizure control according to the Engel classification scheme, durations of the included epochs, the location of seizure onset, etiological factors, the type of resection, the total number of artifact free channels, and the number of channels recording from RBT. Nineteen of these patients were already included in our preceding study ( 32 ) and are indicated by an asterisk *. One patient (p5) had two implantation schemes before resection, one patient (p29) had two distinct implantation schemes both followed by resection, and one patient (p28) had a second implantation after the surgical removal of brain tissue but no second resection .…”
Section: Methodsmentioning
confidence: 99%
“…The qEEG measure used in this study was introduced by Rummel et al ( 34 , 41 ) and has been applied in ( 32 , 42 , 43 ). A similar measure was also used in ( 16 , 27 , 30 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of Müller et al 4 evaluates the linear relationships measured by coherence and the nonlinear relationships measured by mutual information during a 3-minute preictal period in 20 patients with bilateral temporal electrode implantations. Nonlinear measures usually reflect both linear and nonlinear relationships but in this study the nonlinear relationships represent the excess part of the relationship which cannot be explained by linear relationships.…”
Section: Commentarymentioning
confidence: 99%